Magnitude and relevance of change in health-related quality of life in patients with vascular malformations treated with sirolimus - Harbers, Veroniek E. M.; Bouwman, Frédérique C. M.; van Rijnsoever, Ingrid M. P.; Verhoeven, Bas H.; van der Vleuten, Carine J. M.; Schultze Kool, Leo J.; de Laat, Peter C. J.; van der Horst, Chantal M. A. M.; Kievit, Wietske; te Loo, D. Maroeska W. M. (Frontiers in Medicine, 2023)
Vascular malformations are rare congenital anomalies of the vascular system, which can involve the capillaries, veins, arteries, lymphatics, or a combination of vessel types. Patients with vascular malformations experience an impaired health-related quality of life (HRQoL) due to their symptoms (e.g., pain, swelling, bleeding) and psychosocial distress. Sirolimus is an effective medical treatments for these patients; however, relatively little is known about the effect of sirolimus on specific changes in the HRQoL domains and its magnitude. The magnitude of change (effect size) following an intervention is more informative to clinical practitioners than statistically significant but clinically unimportant changes; therefore, the aim of this study was to examine the magnitude and meaningfulness of change in the HRQoL of patients with vascular malformations following sirolimus treatment using low target levels. In total, 50 patients with a vascular malformation (19 children, 31 adults) were included in this study. These patients experienced a lower HRQoL than the general population, with the adults reporting a significantly lower score in almost all domains. A six-month sirolimus treatment improved the HRQoL in 29 patients, including 77.8% of the children (Pediatric Quality of Life Inventory score [PedsQL]) and 57.7% of the adults (Short-Form 36 [SF-36]). The effect sizes of sirolimus for each SF36/PedsQL domain ranged from 0.19 to 1.02. Clinically relevant moderate-magnitude of changes were seen in the children’s reports: ‘Physical functioning’, ‘Social functioning’, and in the parent reports: ‘Social functioning’, ‘School functioning’, and ‘Psychosocial’. A high-magnitude change was seen in ‘Emotional functioning’ and ‘Psychosocial’ in child reports, and ‘Physical functioning’ in the parent reports. In addition, moderate-magnitude of changes were also seen in the adults SF-36: in all domains except for ‘Role limitations - physical problems’, ‘Role limitations - emotional problems’, and ‘General health perception’. We believe this is the first study showing the magnitude of change in HRQoL after sirolimus treatment in children and adults with vascular malformations. Before treatment, these patients experienced an impaired HRQoL compared with the general Dutch population. A six-month sirolimus treatment with low target levels led to moderate-to-high clinically relevant changes in multiple domains, which significantly improved the HRQoL.